2012
DOI: 10.1016/j.cbpc.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Gene-class analysis of expression patterns induced by psychoactive pharmaceutical exposure in fathead minnow (Pimephales promelas) indicates induction of neuronal systems

Abstract: Psychoactive pharmaceuticals are among the most frequently prescribed drugs, contributing to persistent measurable concentrations in aquatic systems. Typically, it is assumed that such contaminants have no human health implications because they exist in extremely low concentrations. We exposed juvenile fathead minnows (Pimephales promelas) to three pharmaceuticals, fluoxetine, venlafaxine and carbamazepine, individually and in a mixture, and measured their effect on the induction of gene expression in fish bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 121 publications
5
70
0
Order By: Relevance
“…7, No. 2;2015 ants will examine effects of antidepressants free of fluoxetine, for checking if these effects (somewhat reported by Brodin, Fick, Jonsson &Klaminder, 2013 andThomas, Joshi &Klaper, 2012) are weaker than those of antidepressants containing fluoxetine, and if physical dependence to them occurs. Let us recall that, in the course of the present experimentation, ants never develop habituation to or dependence on fluoxetine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…7, No. 2;2015 ants will examine effects of antidepressants free of fluoxetine, for checking if these effects (somewhat reported by Brodin, Fick, Jonsson &Klaminder, 2013 andThomas, Joshi &Klaper, 2012) are weaker than those of antidepressants containing fluoxetine, and if physical dependence to them occurs. Let us recall that, in the course of the present experimentation, ants never develop habituation to or dependence on fluoxetine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin may also influence appetite and behavior through modulation of downstream processes including controlling the release of various hormones in fish responsible for regulating growth, stress response, behavior, and reproductive function (Somoza and Peter, 1991;Medeiros et al, 2010;Overli et al, 1999;Winberg and Lepage, 1998;Lowry and Moore, 2006). More specifically, venlafaxine has been shown to decrease egg production in zebra fish (Galus et al, 2013;Mennigen et al, 2009), cause up-regulation of genes indicative of neurodegredation and modulation of action potentials in fathead minnow brains (Thomas et al, 2012), and inhibit both basal and epinephrine induced glucose production in rainbow trout hepatocytes (Ings et al, 2012) which may result in decreased brain serotonin in fish (Ruibal et al, 2002) Behavioral results from this study indicated that venlafaxine has less of an effect than fluoxetine. Fluoxetine concentrations as low as 23 g/L were shown to cause significant reduction in the ability of hybrid striped bass to capture prey 1, 2, and 3 (Gaworecki and Klaine, 2008) while the lowest concentration tested in the current study (35 g/L) only caused a significant effect on the time to capture prey 3.…”
Section: Discussionmentioning
confidence: 98%
“…Venlafaxine has been shown to block epinephrine induced glucose production in rainbow trout (Oncorhynchus mykiss) hepatocytes which may have implications for stress response in exposed fish (Ings et al, 2012). Though uptake of venlafaxine into fish neural tissue has been shown to be limited during environmentally relevant exposures (Schultz et al, 2010;Schultz et al, 2011) gene expression patterns in the brains of fathead minnows exposed to venlafaxine reveal upregulation of genes related to neural development and regulation of action potentials (Thomas et al, 2012). But researchers have yet to examine the targeted outcome of venlafaxine, modulation of serotonin.…”
Section: Introductionmentioning
confidence: 97%
“…These synthetic chemicals may serve as environmental factors that act as a trigger in genetically susceptible individuals [7, 912]. Our study focused on a specific class of potential toxicants, pharmaceuticals and personal care products (PPCP) [13]. PPCPs mainly involved psychoactive pharmaceuticals, which have been detected in the drinking water at low concentrations [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Psychoactive pharmaceuticals are among the most highly prescribed classes of drug in United States [13, 14, 16] and patient excretions still contain active metabolites that have considerably long half-lives [14, 17]. Waste-water treatment plants release PPCP-contaminated water into surface water such as rivers and lakes [17].…”
Section: Introductionmentioning
confidence: 99%